2018
DOI: 10.5194/acp-18-3817-2018
|View full text |Cite
|
Sign up to set email alerts
|

Aircraft and ground measurements of dust aerosols over the west African coast in summer 2015 during ICE-D and AER-D

Abstract: Abstract. During the summertime, dust from the Sahara can be efficiently transported westwards within the Saharan air layer (SAL). This can lead to high aerosol loadings being observed above a relatively clean marine boundary layer (MBL) in the tropical Atlantic Ocean. These dust layers can impart significant radiative effects through strong visible and IR light absorption and scattering, and can also have indirect impacts by altering cloud properties. The processing of the dust aerosol can result in changes i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
117
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(126 citation statements)
references
References 74 publications
8
117
1
Order By: Relevance
“…Nevertheless, the temporal evolution of the particle classes is representative and compares well to the the dust fraction of incandescent particles identified in tandem Soot photometer (SP2) measurement (Liu et al, 2018). …”
mentioning
confidence: 61%
“…Nevertheless, the temporal evolution of the particle classes is representative and compares well to the the dust fraction of incandescent particles identified in tandem Soot photometer (SP2) measurement (Liu et al, 2018). …”
mentioning
confidence: 61%
“…Recently, the SP2 has been increasingly used to quantify other light absorbing refractory aerosols (e.g. Moteki et al (2017); Liu et al (2018)). In particular, observations in source regions have shown that iron oxide containing aerosols from anthropogenic origins are present in the 5 atmosphere (Liati et al, 2015;Dall'Osto et al, 2016;Adachi et al, 2016;Li et al, 2017), and these aerosols can be detected via laser-induced incandescence with an SP2 (Yoshida et al, 2016;Moteki et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Incandescent particles in Icelandic mineral dust and Taklamakan Desert dust also have been detected with low efficiency using the SP2 (Yoshida et al, 2016). An SP2 was used in one study to estimate the hematite content in Saharan dust measured off the West coast of Africa, and demonstrated good closure between 10 the hematite concentration associated with single dust particles and the optical properties observed in the dust plume (Liu et al, 2018). While previous work focusing on anthropogenic FeO x has relied on using the optical size of these aerosols after any volatile coatings have evaporated as an additional criteria to differentiate anthropogenic and non-anthropogenic aerosols with metallic components (Yoshida et al, 2016;Moteki et al, 2017;Yoshida et al, 2018), this method is limited to the range over which the SP2 optically sizes these aerosols (generally limited to ∼170-350 nm volume equivalent diameter 15 for FeO x ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations